High-performance polymer material and application thereof in battery protection

By using a high-performance polymer material in lithium-ion batteries, which consists of component A and component B in a specific ratio, and the addition of flame retardant compound A, polyphosphazene@Ce doped-g-C3N4 composite material and Cu-MOF material, the internal short circuit problem of the battery during local extrusion is solved, and the flame retardant and mechanical properties of the battery are significantly improved, and thermal runaway and fire accidents are prevented.

CN119662018APending Publication Date: 2025-03-21QINGDAO ADVANCED MARINE MATERIAL TECH

Patent Information

Application Number
CN202411974130.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing lithium-ion batteries are prone to internal short circuits during local extrusion, resulting in thermal runaway and fire accidents. In addition, existing polymer materials have problems with insufficient flame retardant and mechanical properties in battery protection.

Method used

A high-performance polymer material is used, which includes component A and component B, which consists of polyoxypropylene polyol D3000, polyether polyol 4110 and isocyanate, and component B is composed of terminal amino polyether, chain extender, flame retardant compound A, polyphosphazene@Ce doped-g-C3N4 composite material and Cu-MOF material. The flame retardant properties and mechanical properties of the polymer material are improved by combining the homemade flame retardant compound A, combined with polyphosphazene@Ce-doped-g-C3N4 composite material and Cu-MOF material.

Benefits of technology

The flame retardant and mechanical properties of polymer materials are improved, so that they can effectively prevent thermal runaway and fire accidents in battery protection, and extend the battery's fire resistance limit.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to a high-performance polymer material and application thereof in battery protection. The high-performance polymer material comprises a component A and a component B. The component A is prepared from the following raw materials in parts by weight: 60-80 parts of polyoxypropylene polyol D3000; 20 to 40 parts of polyether polyol 4110; 40 to 60 parts of isocyanate; the component B is prepared from the following raw materials in parts by weight: 50 to 70 parts of amino-terminated polyether; 40 to 50 parts of a chain extender; 1-3 parts of a dispersant; 2-4 parts of a defoaming agent; 4-8 parts of a flame retardant compound A; 3 to 7 parts of a polyphosphazene coated Ce doped g-C3N4 composite material; and 2 to 6 parts of a Cu-MOF material. The flame retardant compound A is self-made and added in the preparation process, and is matched with the polyphosphazene-coated Ce-doped g-C3N4 composite material and the Cu-MOF material, so that the flame retardant property of the polymer material is improved, the flame retardant property of the polymer material is also improved, and a good protection effect can be achieved in battery protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer materials, and more specifically, relates to a high-performance polymer material and its application in battery protection. Background Art

[0003] Lithium-ion battery cells are usually composed of positive and negative electrode materials and diaphragm materials in a stacked or wound manner. The specific cell structures include square structure, aluminum-plastic film (soft pack) structure and cylindrical structure. Since the capacity and voltage of a single lithium-ion battery cell are limited, multiple battery cells need to be connected in series and parallel to form a battery module. When lithium-ion batteries are locally squeezed, the battery is prone to internal short circuits, causing thermal runaway and fire accidents.

[0004] Polyurea is an elastomeric polymer obtained by the chemical reaction of isocyanate and amino compounds. Due to its anti-corrosion, wear resistance, oxidation resistance, and extremely high tensile strength, it is now widely used as a protective coating structure in vehicles, ships, and buildings.

[0005] CN118308018A discloses a water-based polyurea coating and a preparation method thereof, a water-based polyurea coating and its application, and belongs to the technical field of polyurea coatings. The present invention adds modified polyetheramine to improve the flexibility of the water-based polyurea coating; the present invention uses water as a dispersion medium and will not cause harm to the human body and the environment; the water-based polyurea coating provided by the present invention has very excellent mechanical strength and waterproof and anti-corrosion properties, which improves the safety of new energy vehicle batteries; the water-based polyurea coating of the present invention has good explosion-proof and thermal conductivity. When encountering fire, it will rely on the explosion-proof and thermal conductivity of the coating itself to form a protective layer and dissipate heat in time, delaying the direct invasion of the fire on the new energy battery, thereby effectively improving the fire resistance limit of the new energy battery structure.

[0006] CN113583553A discloses a multifunctional polyurea coating for a power battery tray, and its preparation method and application. The adhesion of the polyurea coating to the substrate is improved by modified isocyanate, thereby improving the impact resistance of the coating; by adding modified carbon nanofibers, modified nano cerium trifluoride and modified nano lanthanum trifluoride, the impact resistance of the polyurea coating is improved, and the coating is super hydrophobic; by adding graphene, the impact resistance of the coating is further improved; by adding flame retardants, the coating has stable and efficient flame retardant properties. The results of the embodiment show that the tensile strength of the multifunctional polyurea coating for a power battery tray provided by the present invention is 40MPa, the elongation at break is 450%, the tear strength is 121kN / m, the contact angle is 153°, the UL-94 flame retardant test is V0, and the adhesion to 45 steel is 16.57MPa.

[0007] CN116200111A discloses a flame retardant and heat insulating polyurea coating for a battery box of a new energy vehicle, and its preparation method and application. The polyurea coating is composed of a component A and a component B which are stored separately; the component A is obtained by vacuuming and stirring polyether polyol and phosphorus-containing polyol at a temperature of 110-120°C, cooling to 60-80°C, passing nitrogen for protection, adding diisocyanate, stirring evenly and then vacuuming; the component B is obtained by stirring polyether amine, chain extender, reactive flame retardant, hollow glass microspheres and isopropanol, and then ultrasonically treating; the polyurea coating prepared by the present invention has excellent flame retardant and heat insulating properties and waterproof and anti-corrosion properties, which can greatly improve the safety of new energy vehicle batteries, and make new energy batteries unaffected by ambient temperature, thereby improving battery life and the endurance of new energy vehicles.

[0008] CN113583553A discloses a multifunctional polyurea coating for a power battery tray, and its preparation method and application. The adhesion of the polyurea coating to the substrate is improved by modified isocyanate, thereby improving the impact resistance of the coating; by adding modified carbon nanofibers, modified nano cerium trifluoride and modified nano lanthanum trifluoride, the impact resistance of the polyurea coating is improved, and the coating is super hydrophobic; by adding graphene, the impact resistance of the coating is further improved; by adding flame retardants, the coating has stable and efficient flame retardant properties. The results of the embodiment show that the tensile strength of the multifunctional polyurea coating for a power battery tray provided by the present invention is 40MPa, the elongation at break is 450%, the tear strength is 121kN / m, the contact angle is 153°, the UL-94 flame retardant test is V0, and the adhesion to 45 steel is 16.57MPa.

[0009] The performance of the polyurea polymer material can be improved by adding a modified component to the polyurea composite material, and it can play a good protective role in battery protection. Therefore, the present invention provides a new high-energy polymer material, which has excellent flame retardant properties and mechanical properties, and can play a good protective role in battery protection. Summary of the invention

[0010] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art and provide a high-performance polymer material and its application in battery protection. The high-performance polymer material includes component A and component B. The raw materials of component A are proportioned by weight as follows: 60-80 parts of polyoxypropylene polyol D3000; 20-40 parts of polyether polyol 4110; 40-60 parts of isocyanate; the raw materials of component B are proportioned by weight as follows: 50-70 parts of amino-terminated polyether; 40-50 parts of chain extender; 1-3 parts of dispersant; 2-4 parts of defoamer; 4-8 parts of flame retardant compound A; 3-7 parts of polyphosphazene@Ce doped-g-C3N4 composite material; 2-6 parts of Cu-MOF material. The present invention adds a self-made flame retardant compound A during the preparation process, and cooperates with the polyphosphazene@Ce doped-g-C3N4 composite material and the Cu-MOF material, which not only improves the flame retardant properties of the polymer material, but also improves the flame retardant properties of the polymer material, and can play a good protective role in battery protection.

[0011] The object of the present invention is to provide a high-performance polymer material.

[0012] Another object of the present invention is to provide an application of a high-performance polymer material in battery protection.

[0013] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0014] A high-performance polymer material comprises a component A and a component B, wherein the raw materials of the component A are proportioned by weight as follows:

[0015] 60-80 parts of polyoxypropylene polyol D3000;

[0016] Polyether polyol 4110 20-40 parts;

[0017] 40-60 parts of isocyanate;

[0018] The raw materials of the B component are proportioned by weight as follows:

[0019] 50-70 parts of amino-terminated polyether;

[0020] 40-50 parts of chain extender;

[0021] 1-3 parts of dispersant;

[0022] 2-4 parts of defoaming agent;

[0023] Flame retardant compound A 4-8 parts;

[0024] Polyphosphazene@Ce doped-g-C3N4 composite material 3-7 parts;

[0025] 2~6 parts of Cu-MOF material;

[0026] The preparation method of the flame retardant compound A comprises the following steps:

[0027] 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 2,4-dihydroxybenzaldehyde are dispersed in ethanol, and then stirred and reacted at 40-50°C for 6-10 hours under nitrogen protection, and then 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) is added, the temperature is raised to 60-70°C, and stirred and reacted for 10-14 hours under nitrogen protection, cooled to room temperature, rotary evaporated at 70-90°C, washed, filtered, and vacuum dried at 70-90°C to constant weight to obtain flame retardant compound A.

[0028] Preferably, the isocyanate is at least one of isophorone diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate; the amino-terminated polyether is amino-terminated polyether D-2000; and the chain extender is one or more of 3,5-dimethylthiotoluenediamine, 2,4-diamino-3,5-dimethylthiochlorobenzene, and N,N′-di-sec-pentylcyclohexanediamine.

[0029] More preferably, the molar ratio of the 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 2,4-dihydroxybenzaldehyde and DOPO is 1:2:2.

[0030] In the present invention, a preferred embodiment of the present invention is that the method for preparing the polyphosphazene@Ce doped-g-C3N4 composite material comprises the following steps:

[0031] (1) dispersing melamine and cerium nitrate in ethanol, stirring, and then performing a solvothermal reaction, cooling to room temperature, washing, and drying to obtain a precursor, and then heat treating under inert atmosphere to obtain Ce-doped g-C3N4;

[0032] (2) Adding the Ce-doped g-C3N4, hexachlorocyclotriphosphazene, o-phenylenediamine and triethylamine obtained in step (1) to acetonitrile, reacting at 150-170°C for 5-7h under N2 protection, filtering, washing and drying to obtain a polyphosphazene@Ce-doped-g-C3N4 composite material.

[0033] Preferably, in step (1), the mass ratio of melamine to cerium nitrate is 1:0.06-0.1; the stirring time is 1-2 hours; the solvent thermal reaction is carried out at 160-200°C for 30-50 hours, the drying is carried out at 80-120°C for 6-10 hours; and the heat treatment is carried out at 400-600°C for 3-5 hours.

[0034] Further preferably, in step (2), the ratio of Ce-doped g-C3N4, hexachlorocyclotriphosphazene, o-phenylenediamine and triethylamine is 1 g: 0.2 mol: 0.4-0.8 mol: 180-220 mL, and the drying is performed at 70-90° C. for 4-8 h.

[0035] In the present invention, a further preferred embodiment is that the method for preparing the Cu-MOF material comprises the following steps:

[0036] The copper source, 2,3,5,6-tetrafluoro-di(1,2,4-triazole-1-methyl)benzene (Fbtx) and 2-methylimidazole were added to ethanol water, and then transferred to a polytetrafluoroethylene-lined reactor for hydrothermal reaction at 160-200°C for 2-4 days, cooled to room temperature, filtered, washed, and dried at 80°C to constant weight to obtain Cu-MOF material.

[0037] Preferably, the volume ratio of the ethanol to water is 1:3; the molar ratio of the copper source, 2,3,5,6-tetrafluoro-bis(1,2,4-triazole-1-methyl)benzene (Fbtx) and 2-methylimidazole is: 1:2~4:1~3, and the copper source is one of copper nitrate, copper chloride and copper acetate.

[0038] In the present invention, a further preferred solution includes the preparation of component A and the preparation of component B.

[0039] The preparation method of component A is as follows:

[0040] Add polyoxypropylene polyol D3000 and polyether polyol 4110 into a reaction kettle, decompress and dehydrate at 95-105°C for 5-7 hours, cool to 45°C, add isocyanate, stir evenly, then heat to 85-95°C, keep warm for 2-4 hours, degas and cool to obtain component A;

[0041] The preparation method of component B is as follows:

[0042] Add amino-terminated polyether, chain extender, flame retardant compound A, polyphosphazene@Ce doped-g-C3N4 composite material, Cu-MOF material, dispersant and defoamer into a reactor, heat to 60-80°C for high-speed dispersion, stir for 20-40 min, rotate at 1100-1300 r / min, and obtain component B.

[0043] Based on the application of a high-performance polymer material in battery protection described above.

[0044] The present invention has the following beneficial effects:

[0045] The present invention obtains a flame retardant compound containing N, Si and P by reacting 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane with 2,4-dihydroxybenzaldehyde and DOPO. The flame retardant compound has good compatibility with polyurea, can play a good smoke suppression effect, and improves the flame retardant effect; the decomposition of g-C3N4 at high temperature can release non-flammable small molecular gases (NH3 and N2) containing nitrogen elements, which can play a gas phase flame retardant effect, and the flame retardant properties of g-C3N4 can be well improved by doping with Ce. Then, by compounding with polyphosphazene, the compatibility of g-C3N4 in polyurea is not only improved, but also the flame retardant properties and mechanical properties are improved; combined with Cu-MOF material, the flame retardant properties and mechanical properties of the polyurea polymer material are further improved, so that it plays a good protective role in battery protection. DETAILED DESCRIPTION

[0046] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0047] The amino-terminated polyether is amino-terminated polyether D-2000; the dispersant is Disperbyk 162; and the defoamer is EfkaPB2001.

[0048] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0049] Example 1

[0050] A high performance polymer material, comprising component A and component B,

[0051] The raw materials of the A component are proportioned by weight as follows:

[0052] 70 parts of polyoxypropylene polyol D3000;

[0053] 30 parts of polyether polyol 4110;

[0054] 50 parts of isocyanate; the isocyanate is isophorone diisocyanate;

[0055] The raw materials of the B component are proportioned by weight as follows:

[0056] 60 parts of amino-terminated polyether;

[0057] 45 parts of a chain extender; the chain extender is 2,4-diamino-3,5-dimethylthiochlorobenzene;

[0058] 2 parts of dispersant;

[0059] 3 parts of defoamer;

[0060] Flame retardant compound A 6 parts;

[0061] Polyphosphazene@Ce doped-g-C3N4 composite material 5 parts;

[0062] 4 parts of Cu-MOF material;

[0063] The preparation method of the flame retardant compound A comprises the following steps:

[0064] 1 mol of 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 2 mol of 2,4-dihydroxybenzaldehyde were dispersed in 150 mL of ethanol, and then stirred and reacted at 45 ° C for 8 h under nitrogen protection, and then 2 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) was added, the temperature was raised to 65 ° C, and stirred and reacted for 12 h under nitrogen protection, cooled to room temperature, rotary evaporated at 80 ° C, washed, filtered, and vacuum dried at 80 ° C to constant weight to obtain flame retardant compound A.

[0065] The preparation method of the polyphosphazene@Ce doped-g-C3N4 composite material comprises the following steps:

[0066] (1) 1 mol of melamine and 0.08 mol of cerium nitrate were dispersed in 150 mL of ethanol, stirred for 1.5 h, and then subjected to solvothermal reaction at 180 °C for 40 h, cooled to room temperature, washed, and dried at 100 °C for 8 h to obtain a precursor, which was then heat treated at 500 °C for 4 h under inert atmosphere to obtain Ce-doped g-C3N4;

[0067] (2) Add 1 g of Ce-doped g-C3N4 obtained in step (1), 0.2 mol of hexachlorocyclotriphosphazene, 0.6 mol of o-phenylenediamine and 200 mL of triethylamine to 300 mL of acetonitrile, react at 160 °C for 6 h under N2 protection, filter, wash and dry at 80 °C for 6 h to obtain a polyphosphazene@Ce-doped-g-C3N4 composite material.

[0068] The preparation method of the Cu-MOF material comprises the following steps:

[0069] 1 mol of copper nitrate, 3 mol of 2,3,5,6-tetrafluoro-bis(1,2,4-triazol-1-methyl)benzene (Fbtx) and 2 mol of 2-methylimidazole were added to 200 mL of ethanol water, where the volume ratio of ethanol to water was 1:3, and then transferred to a polytetrafluoroethylene-lined reactor, hydrothermally reacted at 180°C for 3 days, cooled to room temperature, filtered, washed, and dried at 80°C to constant weight to obtain Cu-MOF material.

[0070] A high-performance polymer material, comprising the preparation of component A and the preparation of component B,

[0071] The preparation method of component A is as follows:

[0072] Add polyoxypropylene polyol D3000 and polyether polyol 4110 into a reaction kettle, dehydrate under reduced pressure at 100°C for 6 hours, cool to 45°C, add isocyanate, stir evenly, then heat to 90°C, keep warm for 3 hours, degas and cool to obtain component A;

[0073] The preparation method of component B is as follows:

[0074] Add amino-terminated polyether, chain extender, flame retardant compound A, polyphosphazene@Ce doped-g-C3N4 composite material, Cu-MOF material, dispersant and defoamer into a reactor, heat to 70°C for high-speed dispersion, stir for 30 min, and rotate at 1200 r / min to obtain component B.

[0075] Example 2

[0076] A high performance polymer material, comprising component A and component B,

[0077] The raw materials of the A component are proportioned by weight as follows:

[0078] 80 parts of polyoxypropylene polyol D3000;

[0079] 20 parts of polyether polyol 4110;

[0080] 60 parts of isocyanate; the isocyanate is diphenylmethane diisocyanate;

[0081] The raw materials of the B component are proportioned by weight as follows:

[0082] 70 parts of amino-terminated polyether;

[0083] 40 parts of chain extender; the chain extender is 3,5-dimethylthiotoluenediamine;

[0084] 3 parts of dispersant;

[0085] 2 parts of defoaming agent;

[0086] Flame retardant compound A 8 parts;

[0087] 3 parts of polyphosphazene@Ce doped-g-C3N4 composite material;

[0088] 6 parts of Cu-MOF material;

[0089] The preparation method of the flame retardant compound A is the same as that of Example 1.

[0090] The preparation method of the polyphosphazene@Ce doped-g-C3N4 composite material comprises the following steps:

[0091] (1) 1 mol of melamine and 0.1 mol of cerium nitrate were dispersed in 150 mL of ethanol, stirred for 2 h, and then subjected to solvothermal reaction at 200 °C for 30 h. The precursor was cooled to room temperature, washed, and dried at 120 °C for 6 h to obtain a precursor. The precursor was then heat treated at 600 °C for 3 h under inert atmosphere to obtain Ce-doped g-C3N4.

[0092] (2) Add 1 g of Ce-doped g-C3N4 obtained in step (1), 0.2 mol of hexachlorocyclotriphosphazene, 0.8 mol of o-phenylenediamine and 220 mL of triethylamine to 300 mL of acetonitrile, react at 170 °C for 5 h under N2 protection, filter, wash and dry at 90 °C for 4 h to obtain a polyphosphazene@Ce-doped-g-C3N4 composite material.

[0093] The preparation method of the Cu-MOF material comprises the following steps:

[0094] 1 mol of copper chloride, 4 mol of 2,3,5,6-tetrafluoro-bis(1,2,4-triazol-1-methyl)benzene (Fbtx) and 1 mol of 2-methylimidazole were added to 200 mL of ethanol water, where the volume ratio of ethanol to water was 1:3, and then transferred to a polytetrafluoroethylene-lined reactor, hydrothermally reacted at 200°C for 2 days, cooled to room temperature, filtered, washed, and dried at 80°C to constant weight to obtain Cu-MOF material.

[0095] A high-performance polymer material includes the preparation of component A and component B. The preparation process of component A and the preparation process of component B are the same as those in Example 1.

[0096] Example 3

[0097] A high performance polymer material, comprising component A and component B,

[0098] The raw materials of the A component are proportioned by weight as follows:

[0099] 60 parts of polyoxypropylene polyol D3000;

[0100] 40 parts of polyether polyol 4110;

[0101] 40 parts of isocyanate; the isocyanate is xylylene diisocyanate;

[0102] The raw materials of the B component are proportioned by weight as follows:

[0103] 50 parts of amino-terminated polyether;

[0104] 50 parts of chain extender; the chain extender is N,N′-di-secondary pentylcyclohexanediamine;

[0105] 1 part of dispersant;

[0106] 4 parts of defoamer;

[0107] Flame retardant compound A 4 parts;

[0108] Polyphosphazene@Ce doped-g-C3N4 composite material 7 parts;

[0109] 2 parts of Cu-MOF material;

[0110] The preparation method of the flame retardant compound A is the same as that of Example 1.

[0111] The preparation method of the polyphosphazene@Ce doped-g-C3N4 composite material comprises the following steps:

[0112] (1) 1 mol of melamine and 0.06 mol of cerium nitrate were dispersed in 150 mL of ethanol, stirred for 1 h, and then subjected to solvothermal reaction at 160 °C for 50 h, cooled to room temperature, washed, and dried at 80 °C for 10 h to obtain a precursor, which was then heat treated at 400 °C for 5 h under inert atmosphere to obtain Ce-doped g-C3N4;

[0113] (2) Add 1 g of Ce-doped g-C3N4 obtained in step (1), 0.2 mol of hexachlorocyclotriphosphazene, 0.4 mol of o-phenylenediamine and 180 mL of triethylamine to 300 mL of acetonitrile, react at 150 °C for 7 h under N2 protection, filter, wash and dry at 70 °C for 8 h to obtain a polyphosphazene@Ce-doped-g-C3N4 composite material.

[0114] The preparation method of the Cu-MOF material comprises the following steps:

[0115] 1 mol of copper acetate, 2 mol of 2,3,5,6-tetrafluoro-bis(1,2,4-triazol-1-methyl)benzene (Fbtx) and 3 mol of 2-methylimidazole were added to 200 mL of ethanol water, where the volume ratio of ethanol to water was 1:3, and then transferred to a polytetrafluoroethylene-lined reactor, hydrothermally reacted at 160°C for 4 days, cooled to room temperature, filtered, washed, and dried at 80°C to constant weight to obtain Cu-MOF material.

[0116] A high-performance polymer material includes the preparation of component A and component B. The preparation process of component A and the preparation process of component B are the same as those in Example 1.

[0117] Comparative Example 1

[0118] The difference between the comparative example 1 and the embodiment 1 is that Ce doping is omitted, and the rest is not repeated here.

[0119] Comparative Example 2

[0120] The difference between Control Example 2 and Example 1 is that an equal amount of Ce-doped-g-C3N4 composite material is used to replace the polyphosphazene@Ce-doped-g-C3N4 composite material, and the rest is not repeated. The preparation method of the Ce-doped-g-C3N4 composite material includes the following steps: dispersing 1 mol of melamine and 0.1 mol of cerium nitrate in 150 mL of ethanol, stirring for 2 h, and then solvent-thermally reacting at 200 ° C for 30 h, cooling to room temperature, washing, and drying at 120 ° C for 6 h to obtain a precursor, and then heat treating at 600 ° C for 3 h under inert atmosphere conditions to obtain Ce-doped g-C3N4.

[0121] Comparative Example 3

[0122] The difference between Control Example 3 and Example 1 is that the preparation method of the Cu-MOF material comprises the following steps: adding 1 mol of copper nitrate and 5 mol of 2,3,5,6-tetrafluoro-di(1,2,4-triazole-1-methyl)benzene (Fbtx) to 200 mL of ethanol water, wherein the volume ratio of ethanol to water is 1:3, and then transferring to a reactor lined with polytetrafluoroethylene, hydrothermally reacting at 180°C for 3d, cooling to room temperature, filtering, washing, and drying at 80°C to constant weight to obtain a Cu-MOF material.

[0123] Comparative Example 4

[0124] The difference between Control Example 4 and Example 1 is that an equal amount of polyphosphazene@Ce doped-g-C3N4 composite material is used to replace flame retardant compound A, and other details are not repeated here.

[0125] Comparative Example 5

[0126] The difference between Control Example 5 and Example 1 is that an equal amount of polyphosphazene@Ce doped-g-C3N4 composite material is used to replace the Cu-MOF material, and the rest is not repeated here.

[0127] The performance of Examples 1-3 and Comparative Examples 1-5 was tested. The specific test method was as follows: Component A and Component B were mixed at a volume ratio of 1:1, stirred evenly, and then mixed evenly by a sprayer and sprayed on the surface of the steel plate until the coating reached the required thickness of 1.5 mm. The tensile strength was tested according to GB / T23446-2009, and the test results are shown in Table 1. The limiting oxygen index was tested according to GB / T 2406-2009, and the test results are shown in Table 2.

[0128] Table 1:

[0129] Example 1 Example 2 Example 3 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Tensile strength (MPa) 21.5 21.2 21.4 20.5 20.8 19.4 18.9

[0130] It can be seen from Table 1 that the high-performance polymer material prepared by the present invention has excellent mechanical properties, wherein the maximum tensile strength can reach 21.5 MPa. Moreover, by comparing the embodiments with the control examples, it can be seen that the components of the present application have a synergistic effect with each other, thereby promoting the improvement of the tensile strength.

[0131] Table 2

[0132] Limiting oxygen index (LOI) / % Limiting oxygen index (LOI) / % Example 1 42.6 Comparative Example 2 40.2 Example 2 41.9 Comparative Example 3 40.6 Example 3 42.3 Comparative Example 4 37.4 Comparative Example 1 41.2 Comparative Example 5 37.9

[0133] It can be seen from Table 2 that the high-performance polymer material prepared by the present invention has excellent flame retardant properties, and the limiting oxygen index can reach up to 42.6%. By comparing Example 1 with the control example, it can be seen that the components selected in the present application and the components have a synergistic effect with each other, can have a good flame retardant effect, and can play a good protective role in battery protection.

[0134] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A high-performance polymer material, comprising component A and component B, characterized in that: The raw materials of the A component are proportioned by weight as follows: 60-80 parts of polyoxypropylene polyol D3000; Polyether polyol 4110 20-40 parts; 40-60 parts of isocyanate; The raw materials of the B component are proportioned by weight as follows: 50-70 parts of amino-terminated polyether; 40-50 parts of chain extender; 1-3 parts of dispersant; 2-4 parts of defoaming agent; Flame retardant compound A 4-8 parts; Polyphosphazene@Ce doped-g-C3N4 composite material 3-7 parts; 2~6 parts of Cu-MOF material; The preparation method of the flame retardant compound A comprises the following steps: 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane and 2,4-dihydroxybenzaldehyde are dispersed in ethanol, and then stirred and reacted at 40-50°C for 6-10 hours under nitrogen protection, and then 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) is added, the temperature is raised to 60-70°C, and stirred and reacted for 10-14 hours under nitrogen protection, cooled to room temperature, rotary evaporated at 70-90°C, washed, filtered, and vacuum dried at 70-90°C to constant weight to obtain flame retardant compound A.

2. A high performance polymer material according to claim 1, characterized in that: The isocyanate is at least one of isophorone diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate; the amino-terminated polyether is amino-terminated polyether D-2000; and the chain extender is one or more of 3,5-dimethylthiotoluenediamine, 2,4-diamino-3,5-dimethylthiochlorobenzene, and N,N′-di-sec-pentylcyclohexanediamine.

3. A high performance polymer material according to claim 1, characterized in that: The molar ratio of the 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane, 2,4-dihydroxybenzaldehyde and DOPO is 1:2:

2.

4. A high performance polymer material according to claim 1, characterized in that: The preparation method of the polyphosphazene@Ce doped-g-C3N4 composite material comprises the following steps: (1) dispersing melamine and cerium nitrate in ethanol, stirring, and then performing a solvothermal reaction, cooling to room temperature, washing, and drying to obtain a precursor, and then heat treating under inert atmosphere to obtain Ce-doped g-C3N4; (2) Adding the Ce-doped g-C3N4, hexachlorocyclotriphosphazene, o-phenylenediamine and triethylamine obtained in step (1) to acetonitrile, reacting at 150-170°C for 5-7h under N2 protection, filtering, washing and drying to obtain a polyphosphazene@Ce-doped-g-C3N4 composite material.

5. A high performance polymer material according to claim 4, characterized in that: In step (1), the mass ratio of melamine to cerium nitrate is 1:0.06-0.1; the stirring time is 1-2 hours; the solvent thermal reaction is carried out at 160-200°C for 30-50 hours, the drying is carried out at 80-120°C for 6-10 hours; and the heat treatment is carried out at 400-600°C for 3-5 hours.

6. A high performance polymer material according to claim 4, characterized in that: In step (2), the ratio of Ce-doped g-C3N4, hexachlorocyclotriphosphazene, o-phenylenediamine and triethylamine is 1 g: 0.2 mol: 0.4-0.8 mol: 180-220 mL, and the drying is performed at 70-90° C. for 4-8 h.

7. A high performance polymer material according to claim 1, characterized in that: The preparation method of the Cu-MOF material comprises the following steps: The copper source, 2,3,5,6-tetrafluoro-di(1,2,4-triazole-1-methyl)benzene (Fbtx) and 2-methylimidazole were added to ethanol water, and then transferred to a polytetrafluoroethylene-lined reactor for hydrothermal reaction at 160-200°C for 2-4 days, cooled to room temperature, filtered, washed, and dried at 80°C to constant weight to obtain Cu-MOF material.

8. A high performance polymer material according to claim 7, characterized in that: The volume ratio of ethanol to water is 1:3; the molar ratio of the copper source, 2,3,5,6-tetrafluoro-bis(1,2,4-triazole-1-methyl)benzene (Fbtx) and 2-methylimidazole is 1:2~4:1~3, and the copper source is one of copper nitrate, copper chloride and copper acetate.

9. A high performance polymer material according to claim 1, characterized in that: Including the preparation of component A and the preparation of component B, The preparation method of component A is as follows: Add polyoxypropylene polyol D3000 and polyether polyol 4110 into a reaction kettle, decompress and dehydrate at 95-105°C for 5-7 hours, cool to 45°C, add isocyanate, stir evenly, then heat to 85-95°C, keep warm for 2-4 hours, degas and cool to obtain component A; The preparation method of component B is as follows: Add amino-terminated polyether, chain extender, flame retardant compound A, polyphosphazene@Ce doped-g-C3N4 composite material, Cu-MOF material, dispersant and defoamer into a reactor, heat to 60-80°C for high-speed dispersion, stir for 20-40 min, rotate at 1100-1300 r / min, and obtain component B.

10. Use of a high-performance polymer material according to any one of claims 1 to 9 in battery protection.

Citation Information

Patent Citations

  • Multifunctional polyurea coating for power battery tray as well as preparation method and application thereof

    CN113583553A

Cited By

  • Multi-hydrogen bond and cross-linked structure synergistically enhanced polyurea as well as preparation method and application thereof

    CN121181838A

  • Polyurea with synergistic reinforcement of multiple hydrogen bonds and crosslinked structure, preparation method and application thereof

    NL4002175A